Student Profiles in Physics Can Affect the Problem-Solving of Students: The Role of Augmented Reality and Problem Based Learning in Supporting Sustainable - Dawana, Irgy Redityo; Prahani*, Binar Kurnia; Hariyono, Eko; Dewangga, Naufal Syafa Aflah; Nisa', Khoirun (Jurnal Pendidikan Sains Indonesia, 2025)
As technology advances and 21st-century skills become increasingly essential, innovative learning methods are crucial for developing students' problem-solving skills (PSS). This research evaluates the PSS profile of high school students in physics by integrating augmented reality (AR) media with a problem-based learning (PBL) model, aligned with SDG 4 (quality education). Using a preliminary qualitative descriptive analysis, data were collected through PSS tests, interviews, and questionnaires. The results reveal that PSS remains underdeveloped: 95 students were categorized as low, 26 as medium, and only 1 as high. Despite understanding the problems, students struggle to provide answers and review solutions, largely due to a lack of independent problem-solving practice. Additionally, the use of technology in schools must be improved. Intensive practice and effective learning models are essential. The implementation of AR technology can enhance learning engagement and outcomes. This study underscores the importance of integrating technology to improve PSS and motivate students, supporting inclusive and quality education as outlined in SDG 4